HAKIKAT EKONOMI SYARIAH (Telaah Prospek dan Problematikanya) - Muh. Haras Rasyid; Ahmad Badwi (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2024)
Starting from the thought that one of the things to do in overcoming life's problems is to rely on the values of Islamic teachings. Of the many values of Islamic teachings, among them are the values that exist in Islamic economics. It is known that Islamic economics is an economic system based on the main teachings of the Qur'an and hadith. Through a study with a simple approach and methodology, this paper underlines that from the nature to the theory and practice of Islamic economics is based on helping and for the benefit of people at all levels of society. Therefore, it is said, Islamic economics has good prospects, because it is not only an alternative and solution, but an economic locomotive in the midst of world economic problems, especially in Indonesia. However, although Islamic economics is an ideal system, especially for Muslims in Indonesia, it is certainly not free from weaknesses or problems in its implementation, both related to human resources as managers, business capital, infrastructure and in competition with conventional economic systems globally.